Modified Power Factor Correction (PFC) Control and Printed Circuit Board (PCB) Design for High-Efficiency and High-Power Density On-Board Charger - Jaeil Baek; Moo-Hyun Park; Taewoo Kim; Han-Shin Youn (Energies, 2021)
This paper presents a modified power factor correction (PFC) ON/OFF control and three-dimensional (3D) printed circuit board (PCB) design for a high-efficiency and high-power density onboard charger (OBC). By alternately operating one of two boost modules of the PFC stage at a 50% or less load condition, the proposed PFC control can reduce the load-independent power loss of the PFC stage, such as core loss and capacitor charging loss of switches. It enables OBCs to have high efficiency across a wide output power range and better thermal performance. The 3D-PCB design decouples a trade-off relationship of the PCB trace design and heat spreader design, increasing the power density of OBCs. A 3.3 kW prototype composed of an interleaved totem-pole bridgeless boost PFC converter and full-bridge (FB) LLC converter has been built and tested to verify the proposed PFC control and 3D-PCB effectiveness design. The prototype has 95.7% full power efficiency (98.2% PFC stage efficiency) and 52 W/in3 power density.